Flipped Classroom Research: From "Black Box" to "White Box" Evaluation - Christian Stöhr; Tom Adawi (MDPI AG, 2018)
The flipped (or inverted) classroom model has gained increasing interest among university teachers in recent years. In the flipped classroom approach, students are encouraged to watch short video lectures as preparation for class, and classroom time is dedicated to more active forms of learning. In this editorial, we provide a thumbnail sketch of the origins and concept of the flipped classroom followed by a summary of the contributions to this special issue, which highlight the importance of considering a range of individual as well as contextual factors when implementing and evaluating the flipped classroom approach. Based on this observation, we propose and briefly discuss realist evaluation as a promising approach to evaluating educational interventions and for advancing our theoretical understanding of the flipped classroom. We argue that realist evaluation provides an analytical framework for posing the next generation of questions about the flipped classroom and we encourage scholars to address the questions: "How or why does the flipped classroom work, for whom, and in what circumstances?"